Prosedur Pengurusan Shifting Permit Kapal MT. Southern Koala di Dermaga Khusus KSOP Dumai - Fauzi Hizkia Tumanggor; Capt. Suratni Ginting; Yuna Sutria (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This paper discusses the procedures for MT ship permit transfer documents. Southen Koala from Special Pier PT. Sari Dumai Oleo towards PT Special Pier. Sari Dumai Sejati at the Class I Dumai Harbormaster and Port Authority Office by PT. Bahari Eka Nusantara Dumai Branch. The methods used in this research are the field method (field research) and the library method (library research). Based on the research results above, it can be concluded that the MT ship Shifting Permit Document Procedure. South Koala from PT special pier. Sari Dumai Oleo towards PT special pier. Sari Dumai Sejati at the Class I Dumai Harbormaster and Port Authority Office by PT. Bahari Eka Nusantara Dumai Branch, is a complex process and involves various parties. This process starts from submitting documents, verification, to implementation permits in the field. The ship movement permit process must comply with the regulations and procedures of PT. Bahari Eka Nusantara ensures the Dumai Branch for safety and smooth operations.